Analysis of Soil Quality Index on Agricultural Land Potato (Solanum tuberosum L.) in Tosari Pasuruan - Retno Tri Purnamasari; Ahmad Zainul Arifin; Anggun Yanuar; Ratna Zulfarosda; Fajar Hidayanto (SEAS (Sustainable Environment Agricultural Science), 2024)
Most Indonesians work in the agricultural sector, making Indonesia included in the category of an agricultural country. Agriculture has an important role in the welfare of the Indonesian population because natural conditions suitable for farming increase the quality and quantity of agricultural products. This research aims to determine the soil quality index of andisol on potato (Solanum tuberosum L.) agricultural land in Tosari sub-district, Pasuruan district, East Java. The research was carried out in Tosari sub-district, Pasuruan district at an altitude of 1700 meters above sea level. In September 2023 – January 2024. This research uses a random purposive sampling method for taking soil samples. Next, it was analyzed in the laboratory for texture, volume weight, porosity, C-organic, pH, P-available, K-exchangeable and root depth was measured. The soil quality index is calculated using the criteria of Mausbach and Seybold (1998), which can be adjusted to field conditions using the Minimum Data Set (MDS). Based on the research results, it was found that the Soil Quality Index (SQI) of potato fields in Tosari sub-district has two criteria, namely medium and good criteria. Ledoksari Village, Kandangan Village, and Podokoyo Village are classified as Good (G) while Ngawidono Village and Mororejo Village are classified as Medium (M).